Pembuatan Zat Pewarna Nabati Dari Kunyit - Budi Utami (Balai Besar Kimia dan Kemasan, 1987)
Turmeric is useful as medicine, spices and pigment. A plant cultivated extensively inIndia, Ceylon and Indonesia. Turmeric pigment consist of the dried, boiled and grinded rhixomes of Curcumalonga. Turmeric pigment have more benefit than synthetic pigment.